The possffiilities of port infrastructure investigations and development - Paulauskas, Vytautas; Paulauskas, Donatas (Transport, 2003)
Transport infrastructure development is based on cargo and passenger flows and the use of new technologies and technique can increase transport safety, optimize time of construction and decrease costs. Some of the new technologies of port infrastructure development and quality control technique and methods are presented in the paper.First Published Online: 19 Dec 2011